2008
DOI: 10.1055/s-2008-1065329
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin as an Acute-phase Reactant during Postoperative Stress Response

Abstract: Ghrelin is a growth hormone-releasing peptide, discovered in 1999 by Kojima et al. Its potential role in inflammation and stress response is not yet clear. The purpose of this study was to characterize perioperative levels of circulating ghrelin in relation to different surgical procedures. The authors compared plasma ghrelin changes with cortisol, cytokines, and acute-phase proteins. The prospective study was performed on 22 patients with resection for colon cancer (group 1). Group 2, functioning as a compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…For example, ghrelin concentrations rise acutely after major surgery along with inflammatory cytokines like tumor-necrosis factor-alpha and interleukin (IL)-6 [569]. In mice, transgenic knockdown of the ghrelin receptor accentuates adverse effects of chronic social-defeat stress [570].…”
Section: Multifaceted Actionsmentioning
confidence: 99%
“…For example, ghrelin concentrations rise acutely after major surgery along with inflammatory cytokines like tumor-necrosis factor-alpha and interleukin (IL)-6 [569]. In mice, transgenic knockdown of the ghrelin receptor accentuates adverse effects of chronic social-defeat stress [570].…”
Section: Multifaceted Actionsmentioning
confidence: 99%
“…Previous studies have revealed that circulating ghrelin levels, especially acyl ghrelin levels, fall in response to abdominal surgery and that the levels gradually recover over 24 hours. [22][23][24][25] We also found that ghrelin levels followed this pattern. However, our results were more complex and difficult to interpret.…”
Section: Discussionmentioning
confidence: 51%
“…[18][19][20][21] Circulating ghrelin levels, especially active ghrelin levels, decrease under conditions of abdominal surgery 22,23 and gradually normalize over 24 hours. 22,24,25 Therefore, the decrease of ghrelin after surgery could be a key driver of POI. Therapeutic effects of ghrelin and ghrelin receptor agonists have been shown on surgeryinduced POI.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease was accompanied by a delay of gastric emptying and a reduction of food intake (Stengel et al, 2011a). Interestingly, in humans an increase of total ghrelin was observed at 24 h post surgery compared to preoperative levels (Maruna et al, 2008), a difference that remains to be further investigated.…”
Section: Alterations Of Circulating Ghrelin By Stress or Immune Challmentioning
confidence: 99%